Evaluation of genetic parameters of 23 autosomal STR loci in a Southern Chinese Han population - Hai-xia Li; Dan Peng; Ying Wang; Ri-ga Wu; Yin-ming Zhang; Ran Li; Hong-yu Sun (Annals of Human Biology, 2018)
Aim: To evaluate the 23 autosomal short tandem repeat (STR) loci included in GoldenEye™ 25 A kit using forensic human identification and paternity testing. Subjects and methods: In total, 3751 unrelated individuals from the Southern Chinese Han population were genotyped with the 5-dye GoldenEye™ 25 A multiplex amplification system. PCR products were separated using arrayed capillary electrophoresis. Allele frequencies and forensic parameters for the 23 autosomal STR loci were statistically analysed. Results: A total of 344 alleles were observed, with corresponding allelic frequencies ranging from 0.0001–0.5519 for the 23 STR loci. No significant deviation from the Hardy-Weinberg equilibrium and linkage disequilibrium was observed. The combined power of discrimination (CPD) was 1–1.6290 × 10−28 and the combined power of exclusion (CPE) was 0.999 999 999 89 and 0.999 999 286 93 for trio and duo cases, respectively. From 3865 meioses, 87 mutation events were discovered. The mutation rate varied from 0–0.00285 for each locus. One-step mutation accounted for 94.25% of total mutations. The ratio of paternal vs maternal mutation was 3.76:1.13 kinds of n/(n + 1) heterozygote genotypes were observed. Conclusions: The results show that 23 STR loci of GoldenEye™ 25 A kit are highly polymorphic in the Southern Chinese Han population, indicating the kit is suitable for forensic application.